2019
DOI: 10.25159/1998-8125/3868
|View full text |Cite
|
Sign up to set email alerts
|

The Value Relevance of Aged Goodwill: A South African Study

Abstract: The purpose of this study was to determine whether goodwill, which is measured in accordance with International Financial Reporting Standard 3 (IFRS 3), is value relevant at acquisition and as time progresses, for a period of two years after acquisition. Using the Ohlson model, 126 JSE firm-year observations were tested. It was subsequently found that goodwill was not value relevant at acquisition date but did become value relevant as time progressed. The possible reasons for goodwill not being value relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(114 reference statements)
1
2
0
Order By: Relevance
“…2. The explanatory power of our model is similar or even higher than other relevance studies such as Oliveira, Rodrigues and Craig, (2010); Omarjee, Yasseen and Mohamed (2019); Li and Taylor (2018). …”
Section: Notessupporting
confidence: 82%
See 1 more Smart Citation
“…2. The explanatory power of our model is similar or even higher than other relevance studies such as Oliveira, Rodrigues and Craig, (2010); Omarjee, Yasseen and Mohamed (2019); Li and Taylor (2018). …”
Section: Notessupporting
confidence: 82%
“…They reported that goodwill acquired within-year is not value relevant in contrast to older goodwill balance. Similarly, Omarjee et al (2019) concluded that in South Africa only 2 years ahead goodwill is value relevant, since investors value its subsequent measurement rules implemented by the impairment testing. Additionally, their results suggested that current-year goodwill accounting balances are not value relevant because of the increased complexity of both goodwill's nature and fair value measurement of transferred assets and liabilities of the acquired business.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…This mandated the use of the purchase method and eliminated the amortisation of goodwill over the assessed useful life instead requiring an annual impairment test. International studies indicating that this change has been value relevant are supported by studies by Eloff and de Villiers (2015) and Omarjee and Garnett (2017) that indicates this also applies in the South African context.…”
Section: Theoretical Backgroundmentioning
confidence: 87%